CLASSIFICATION OF PROBLEMS ENCOUNTERED IN THE TRANSLATION PROCESS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This thesis discusses some syntactic phenomena encountered in the process of translation of works of fiction in French and Uzbek, a comparative analysis of their similarities and differences, and a proposal for strategies for preserving or adapting these phenomena.